Spiraea prunifolia var. simpliciflora leaves ameliorate inflammatory responses and oxidative stress in PPE/LPS-induced chronic obstructive pulmonary disease mouse model - Lee, Ba-Wool; Ha, Ji-Hye; Yi, Da-Hye; Kim, Ju-Hong; Jeong, Seong-Hun; Lee, Hyeon Jin; Kim, Yun-Hye; Kwon, Hyung-Jun; Park, Ji-Young; Kim, Woo Sik; Ryu, Young-Bae; Lee, In-Chul (Frontiers in Pharmacology, 2025)
Spiraea prunifolia: var. simpliciflora (SP) is a known medical food that is used to treat emesis, malaria, and fever. This study investigated the therapeutic potential of SP leaf extract on oxidative stress and airway inflammation using a chronic obstructive pulmonary disease (COPD) mouse model induced by porcine pancreatic elastase (PPE) and lipopolysaccharide (LPS). Male C57BL/6N mice were treated intratracheal instillation of PPE (0.05 units/50 μL) and LPS (5 μg/50 μL), and administered positive control (dexamethasone; 3 mg/kg) and SP (50 and 100 mg/kg). SP treatment decreased T helper type 1 (Th-1) cytokines as well as counts of macrophage and neutrophil in bronchoalveolar lavage fluid of PPE/LPS-induced COPD. SP treatment reduced alveolar destruction, inflammatory cell infiltration, and collagen fiber with improvement of forced expiratory volume to forced vital capacity ratio and lung elastance in lung tissue. SP downregulated thioredoxin-interacting protein and NOD-like receptor pyrin domain-containing 3 inflammasome which inhibited caspase-1 and IL-1β expression. SP attenuated production of reactive oxygen and nitric oxide through enhancement of nuclear factor-erythroid 2-related factor translocation with elevation of heme oxygenase-1 and NAD(P)H quinone oxidoreductase 1 expression. Furthermore, SP attenuated the levels of reactive oxygen species and nitric oxide in mice with PPE/LPS-induced COPD. Thus, SP has the therapeutic potential for COPD treatment.